The research of the emulgating ability of the chia seeds meal pellets and psyllium cellular tissue and the endurance of the emulsions based on them - Krepak, Victoria; Strashynskyi, Igor; Pasichnyi, Vasyl (My University, 2020)
The conducted analysis of the literature sources let us claim about the necessity & the perspective of using of the food ingredients in the body of the frozen meat ground semi-cooked products. It is known that the molecules of polysaccharides are the chains rolled in a ball, which in case of getting into the water or in the surrounding, containing free wet, can unroll, thereby restricting the moving ability of the water molecules. It comes to the increasing of the solution viscosity. Проведений аналіз літературних джерел дозволить стверджувати про необхідність та перспективу вживання харчових інгредієнтів у вигляді заморожених м’ясних напівфабрикатів. Відомо, що молекули полісахаридів – це ланцюжки, згорнуті в клубок, які у разі потрапляння у воду або в навколишнє середовище, що містять вільну вологу, можуть розгортатися, обмежуючи тим самим рухливу здатність молекул води. Йдеться про збільшення в’язкості розчину.
Keywords: fiber; chia seeds; emulsions; клітковина; насіння чіа; емульсії; кафедра технології м’яса і м’ясних продуктів